Accounting control best practices - Bragg, Steven M. (Hoboken, N.J. : Wiley, 2009)
A comprehensive, well-organized reference manual that is perfect for managers and auditors of public and private companies. Whether you wish to comply with the rigors of the Sarbanes-Oxley Act or take your company to the next level, Accounting Control Best Practices, Second Edition contains virtually everything you'll need to design, challenge, and improve your company's internal control environment.
Introduction -- Controls for accounts payable best practices -- Controls for order entry, credit, and shipment best practices -- Controls for inventory management best practices -- Controls for billing best practices -- Controls for collections -- Controls for cash-handling best practices -- Controls for payroll best practices -- Controls for fixed assets best practices -- Controls for budgeting -- Controls for financial reporting.
Series from jacket.
Includes index.
APPSCIE, NBK
1
Keywords: Accounting; Controllership